Monetary Union in West Africa (ECOWAS) - Pattillo, Catherine (Occasional Papers; Occasional Paper, 2001)
This chapter evaluates whether a monetary union makes economic sense and discusses the institutional requirements for a successful Monetary Union in West Africa (ECOWAS). The chapter considers how best the political momentum for a union can be channeled toward a fundamental improvement in underlying policies. The paper also reviews the economic situation of the ECOWAS members, with the objective of evaluating the ease with which they can proceed to a common currency. Regional integration resulting in greater trade among ECOWAS countries may help increase efficiency of production. Trade among developing countries, in general, is likely to have fewer efficiency benefits than trade with developed countries, however, because the possibilities of exploiting complementarities are less. The foregoing considerations suggest that the momentum in favor of monetary union should be channelled into the crucial first phase of enhanced mutual surveillance and emphasis on each country improving its macroeconomic and structural policies. Success in this endeavor would in and of itself help to increase exchange rate stability.